Reaching for the moon - Aldrin, Buzz (HarperCollins Children's Books, 2005)
I Walked on the Moon. This is my journey. It didn't begin when I stepped on board Apollo 11 on July 16, 1969. It began the day I was born -- Edwin Eugene Aldrin Jr., whom everyone called Buzz. Becoming an astronaut took more than education, discipline, and physical strength. It took years of determination and believing that any goal is possible -- from riding a bike alone across the George Washington Bridge at age ten to making a footprint on the Moon. I always knew the Moon was within my reach -- and that I was ready to be part of the team that would achieve the first landing. But it was still hard to believe when I took my first step onto the Moon's surface. We all have our own dreams -- this is the story of how mine came true.